Juvenile probation officers’ lived experiences of collaboration with clinical mental health counselors: An interpretive phenomenological analysis - Gantt, Henrietta Shannon (Journal of addictions & offender counseling, 2025)
This study uses interpretive phenomenological analysis to explore juvenile probation officer's lived experiences of collaborating with counselors. Findings reveal an overview of and the strengths and limitations of existing collaboration. Findings include three higher constructs (a system of multiple parties and arenas, a screening and referral process, and antagonists to collaboration). Super-ordinate themes include intentional initiation, consistent and responsible communication, and culturally and systemically aware counseling. Subordinate themes include networking and setting relational expectations, reporting information and problem solving, and no judgment and reducing barriers. Direct implications for practicing counselors and future research are provided.